Biological aspects and mating behavior in Leucothyreus albopilosus (Coleoptera) - Rodrigues, Sergio Roberto; Ferreira, Kleyton Rezende; Gomes, Elias Soares (Revista de Biología Tropical, 2016)
Members of the genus Leucothyreus Macleay, are little investigated, therefore, studies were conducted in the municipality of Aquidauana and Cassilândia, Mato Grosso do Sul State, Brazil, to analyze the biological aspects and mating behavior in Leucothyreus albopilosus. Adults were captured in a light trap. Afterwards, they were sexed and couples were isolated in the laboratory for reproduction and mating behavior. The biological studies started from eggs under laboratory conditions. In the field, we observed that adults were collected mostly in warmer and wetter periods, from August to March. The embryonic period of L. albopilosus lasted 20.5 days, the 1st, 2nd and 3rd instars lasted 31.0, 33.1 and 85.6 days, respectively. The pupal stage lasted 20 days and the egg to adult period was completed in 185.5 days. These results suggest that L. albopilosus can be characterized as univoltine specie. In laboratory, the adults performed the flying action after the sunset and normally the male seeks the female to start mating. The copulations occurred from 19:00 to 23:00 hours and lasted 19,45 minutes in average. The female is able to refuse the male in order to not start the copulation process. Adults were observed feeding on ripe bananas (Musa sp., Musaceae) and on mangaba flowers (Hancornia speciosa, Apocynaceae).